Intervention Proposals for Reducing Psychological Violence in School Settings: A Literature Review - Herrera Navas, Cristopher David (2025)
Psychological violence in the school environment has become one of the main educational issues, transcending all existing forms of violence, which has positioned it as a cultural and multicausal phenomenon of shared interest. The aim of this research was to analyze the documented intervention proposals for reducing psychological violence in educational contexts. An interpretive documentary approach was used, following the PRISMA protocol, to conduct a bibliographic review. The study analyzes 15 proposals developed for the prevention of psychological violence, highlighting their objectives, contexts, sample populations, key results, and conclusions. It is concluded that most intervention proposals for addressing psychological violence in educational contexts share common elements in their development, including: 1) a clear understanding of the specific issue; 2) the integration of the proposal into the curriculum; 3) continuous evaluation and monitoring; 4) assertive participation from the educational community; 5) a focus on improving the socio-emotional competencies of the educational community; 6) a culture of social intervention within the community for the common good; 7) the sustainability of the intervention in the long term. Therefore, it can be stated that preventing psychological violence requires a cultural, holistic, continuous, and integrative change.